The Statistical Methods for Precipitation Prediction with Trend Analysis - Şevgin, Fatih (Fırat University, 2025)
This study investigates the condensation of water vapor in the atmosphere, precipitating to the ground in either solid or liquid form. This meteorological variable exhibits temporal and spatial variations influenced by climate change and other factors. To better analyze the effects of climate change on precipitation, the Konya Closed Basin was selected as the research area. Key parameters and datasets critical for various sectors and activities—from hydraulic structure design to irrigation planning—were identified. Seasonal and annual precipitation trend analyses were conducted for the provinces of Aksaray, Ankara, Isparta, Mersin, and Nevşehir using statistical methods, including the Mann-Kendall test, Spearman’s Rho, and the Innovative Şen Test, with the aid of XLSTAT software. The results revealed negative precipitation trends in Aksaray, Ankara, and Nevşehir, while positive trends were observed in Isparta and Mersin. Additionally, complementary data were collected from the Muş Meteorology Provincial Directorate to support the findings.

Bu çalışmada atmosferdeki su buharının yoğunlaşması ve daha sonra katı veya sıvı formda yere çökmesi araştırılmıştır. Bu meteorolojik değişken, iklim değişikliği ve diğer faktörlerden etkilenen zamansal ve mekansal değişimler göstermektedir. İklim değişikliğinin yağış üzerindeki etkilerini daha iyi analiz edebilmek için Konya Kapalı Havzası araştırma alanı olarak seçilmiştir. Hidrolik yapı tasarımından sulama planlamasına kadar çeşitli sektörler ve faaliyetler için kritik öneme sahip anahtar parametreler ve veri kümeleri belirlenmiştir. Mann-Kendall testi, Spearman’s Rho ve Yenilikçi Şen Testi gibi istatistiksel yöntemler kullanılarak Aksaray, Ankara, Isparta, Mersin ve Nevşehir illeri için mevsimsel ve yıllık yağış eğilimi analizleri XLSTAT yazılımının yardımıyla gerçekleştirilmiştir. Sonuçlar Aksaray, Ankara ve Nevşehir’de olumsuz yağış eğilimleri ortaya koyarken, Isparta ve Mersin’de olumlu eğilimler gözlenmiştir. Ayrıca bulguları desteklemek için Muş Meteoroloji İl Müdürlüğü’nden tamamlayıcı veriler toplanmıştır.
Trend Analizi ile Yağış Tahmini için İstatistiksel Yöntemler
Keywords: Civil Engineering (Other); İnşaat Mühendisliği (Diğer)